Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae) - Wang, Xingmin; Escalona, Hermes E.; Ren, Shunxiang; Xiaosheng, Chen (Zootaxa, 2017)
The Chinese species of the genus Sticholotis Crotch are described, a key for their identification is provided and most of the species are illustrated. The number of Chinese species of Sticholotis was increased from fourteen to fourty-four. Twenty-five species were newly described: S. acutifolia Wang & Ren sp. nov., S. brachyloba Wang & Ren sp. nov., S. clavata Wang & Ren sp. nov., S. crassa Wang & Ren sp. nov., S. dadugangensis Wang & Ren sp. nov., S. denticuligera Wang & Ren sp. nov., S. dilatata Wang & Ren sp. nov., S. flammula Wang & Ren sp. nov., S. illecebrosa Wang & Ren sp. nov., S. jinpingensis Wang & Ren sp. nov., S. latissima Wang & Ren sp. nov., S. magnopunctata Wang & Ren sp. nov., S. maolanensis Wang & Ren sp. nov., S. nanlingensis Wang & Ren sp. nov., S. neckiformis Wang & Ren sp. nov., S. obesa Wang & Ren sp. nov., S. octopunctata Wang & Ren sp. nov., S. pengi Wang & Ren sp. nov., S. robusta Wang & Ren sp. nov., S. simplifulva Wang & Ren sp. nov., S. taenia Wang & Ren sp. nov., S. tenuis Wang & Ren sp. nov., S. tortus Wang & Ren sp. nov., S. wenchangia Wang & Ren sp. nov. and S. wuzhishana Wang & Ren sp. nov. Five species were newly recorded: S. vietnamica Hoàng, S. carinica (Gorham), S. hoabinhensis Hoàng, S. cinctipennis Weise from Yunnan Province and S. denticulata Hoàng from Guangxi Province.